Evaluation of total antioxidant status, total oxidant status and oxidative stress index in some economically important plants from Turkey - Caf, Fatma; Kiliç, Ömer; Algül, Sermin (Progress in Nutrition, 2018)
This study aims to develop antioxidant properties of thirty four economically important plants of Asteraceae and Lamiaceae families, from Turkey. Analyses were done with reliable measurement research kits. Total antioxidant status, total oxidant status were determined with a novel method using available enzyme-linked immuno assay kit (TOS Cat. No: RL0024, TAS Cat. No: RL0017).Total antioxidant (TAS) level of studied Asteraceae and Lamiaceae taxa were detected as 71.61±37.05 mmol/L and 36.97±9.6 mmol/L, respectively. In addition, TAS level of Asteraceae taxa was found to be higher (p<0.38) than Lamiaceae taxa. When compared total oxidant (TOS) level of Asteraceae (3.02±0.66) and Lamiaceae taxa (5.26±1.06), no significant (p=0.08) differences were observed. In the similar way OSI levels in the Asteraceae (12.52±3.63 AU) Lamiaceae families (30.8±8.4 AU) were found to be no significant difference (p=0.05). The present study concluded that antioxidative feature of studied plant taxa is remarkable. So studied plant taxa are emerges a natural source of antioxidants and could be a good experimental system for further researches.